An evaluation of students' performance in poster presentations using fuzzy evaluation method / Khairu Azlan Abd Aziz ... [et al.] - Abd Aziz, Khairu Azlan; Mohd Idris, Mohd Fazril Izhar; Wan Daud, Wan Suhana; Sudin, Muhamad Amirul (UiTM Cawangan Perlis, 2021)
Poster presentation encompasses many elements such as the organization of poster, the content related to the title proposed, the appearance and the written word. Usually, the poster presentation is used as a platform for student to present their final year project or any other competitions. Students will be evaluated based on the criteria that meets the requirements proposed by the panels or judges. However, their performance in poster presentations does not provide the suitable techniques to estimate the actual value since it involves the elements of fuzziness. In this study, the fuzzy evaluation technique will be applied to measure the performance of the poster presentation. The motivation behind poster presentation is to determine the performance of students using fuzzy evaluation method. The objective of this study is to compare the results between using conventional method and fuzzy evaluation method. The method consists of normalizing the marks, developing the graph of fuzzy membership function, calculating the degree of satisfaction, and finalizing the actual marks. We believed that the result from this study could be able to measure the better output with the consideration of linguistic terms includes excellent, good, moderate, satisfactory, and so on. This method also can be an alternative way to evaluate the performance of the poster presentation.